2008
DOI: 10.1177/039463200802100304
|View full text |Cite
|
Sign up to set email alerts
|

A Quercetin Containing Supplement Reduces Niacin-Induced Flush in Humans

Abstract: Coronary artery disease is associated with increased serum levels of cholesterol, triglycerides and LDL, but low levels of HDL. The most potent agent capable of reversing this trend is the vitamin nicotinic acid (niacin). However, compliance even with extended-release preparations and addition of acetylsalicylic acid (ASA) is hampered by the development of a feeling of erythema and burning ("flush"), especially on the face. We recently showed that the natural flavonoids quercetin and luteolin can eliminate "fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 35 publications
0
19
0
1
Order By: Relevance
“…furthermore, at best, hourly subjective scales only provide a coarse profile of the time course of drug effects. finally, several natural food components have been touted to attenuate NASTy based on very small sample sizes using semi-quantitative scales (59,60). Short of much larger and costlier clinical trials, the efficacy of such measures might be confirmed/ refuted more readily by objective NASTy quantification techniques, with relatively smaller sample sizes.…”
Section: Objective Measurements Of Physical Stigmata Predict Subjectimentioning
confidence: 99%
“…furthermore, at best, hourly subjective scales only provide a coarse profile of the time course of drug effects. finally, several natural food components have been touted to attenuate NASTy based on very small sample sizes using semi-quantitative scales (59,60). Short of much larger and costlier clinical trials, the efficacy of such measures might be confirmed/ refuted more readily by objective NASTy quantification techniques, with relatively smaller sample sizes.…”
Section: Objective Measurements Of Physical Stigmata Predict Subjectimentioning
confidence: 99%
“…Since this extract contains quercetin compounds, it is believed that part of this activity is dependent on this flavonoid. Similarly, in a mouse and human model of niacin-induced flush, quercetin effectively eliminated the flush associated with plasma production of PGD 2 [30]. Another component of grapes and wine is gallic acid which inhibits the proliferation of a mouse mastocytoma cell line (MC/9) [31] by inducing the expressing of pro-apoptotic Bax expression [32].…”
Section: Pinus Pinastermentioning
confidence: 99%
“…119 Os flavonoides quercetina e luteolina foram capazes de eliminar a ruborização, em cobaias, causada pela ação da PGD(2) induzida por ácido niacínico e de reduzir a liberação da serotonina de plaquetas. 119,120 Uma revisão crítica recente sobre a contribuição do metabolismo das prostaglandinas para a saúde da parede vascular sugere que alguns dos efeitos benéficos da niacina poderiam resultar na ativação dos mesmos caminhos metabólicos responsáveis pelos efeitos adversos. Dessa forma, foi concluído que o uso de antagonistas do receptor de PGD(2) e PGE deve ser visto com cautela, já que a vasodilatação dos vasos periféricos poderia ser crucial para a ação aterotrombótica do ácido niacínico.…”
unclassified